2005
DOI: 10.1071/ea04050
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and water availability effects on radiation and water use efficiencies in alfalfa (Medicago sativa L.)

Abstract: Alfalfa, the most important forage crop in Argentina, shows considerable variability in forage production caused by variations in inter-annual rainfall and intra-annual radiation and temperature regimes. Such variation may affect radiation use efficiency and water use efficiency. This paper seeks to study the effects of temperature and water availability on radiation use efficiency and water use efficiency. We conducted the experiment in Córdoba, Argentina, under irrigated and droughted conditions. Drought was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 23 publications
2
20
1
Order By: Relevance
“…In this experiment, WUE increased with the decreasing irrigation level; this varying trend was also found in some studies [21,32,60]. Erice et al [61] found that the WUE increased under a drought of 14 days and declined after a recovery period.…”
Section: Water Use Efficiencymentioning
confidence: 53%
“…In this experiment, WUE increased with the decreasing irrigation level; this varying trend was also found in some studies [21,32,60]. Erice et al [61] found that the WUE increased under a drought of 14 days and declined after a recovery period.…”
Section: Water Use Efficiencymentioning
confidence: 53%
“…Physical and chemical soil characteristics may explain this variability, as the lowest annual value corresponded to the site with coarser texture and lower fertility (Site 4) compared to sites with the highest WUE (Sites 1 and 2; Table 1). Additionally, WUE spatial variability may be due to differences in vapor pressure deficit (VPD) among sites (Collino et al, 2005), since increasing the leafto-air water VPD results in stomatal closure (Schulze and Hall, 1982;El-Sharkawy, Cock and Held, 1984). No differences were found in WUE between seasons at Sites 1, 3 and 4 ( Figure 6).…”
Section: Resultsmentioning
confidence: 84%
“…Seasonal variability of lucerne production was positively associated with intercepted radiation (Collino, Dardanelli, De Luca and Racca, 2005;Brown, Moot and Teixeira, 2006;Mattera, Romero, Cuatrín, Cornaglia and Grimoldi, 2013). Positive relationships between lucerne growth and evapotranspiration have been reported (Saeed and ElNadi, 1997;Singh et al, 2007), although these relationships are generally site and cultivar specific.…”
Section: Introductionmentioning
confidence: 97%
“…Collino et al (2005) reported WA values between 12.0 and 15.0 t ha −1 MJ −1 m −2 for field grown alfalfa in Argentina and Whitfield et al (1986) reported a WA value of 17.2 t ha −1 MJ −1 m −2 . Confalonieri and Bechini (2004) used 30.0 for a WA value after calibrating CropSyst for use in northern Italy.…”
Section: Estimates and Reasonablenessmentioning
confidence: 99%